Comparative pharmacokinetics of verapamil and norverapamil in normal and ulcerative colitis rats after oral administration of low and high dose verapamil by UPLC-MS/MS. (2nd June 2020) - Yao, Hongping; Wang, Changhe; Lu, Wen; Li, Wen; Jing, Wanghui; Zhang, Jiye; Yang, Guangde; Zeng, Aiguo
Abstract: In this study, UC rat model was established by administration of 5% (w/v) dextran sulfate sodium, and the pharmacokinetics of verapamil and norverapamil were evaluated in normal and UC rats using UPLC-MS/MS after oral administration of 5 mg/kg and 50 mg/kg verapamil. The peak concentration (Cmax ) and the area under plasma concentration–time curves (AUC) of verapamil in UC rats after oral administration of 5 mg/kg were significantly greater (2.5 times and 2 times, respectively) than those in normal rats, but the clearance rate (Cl) was significantly lower (by 50%). For norverapamil, Cmax and AUC were significantly greater (2.8 times and 2.5 times, respectively), and Cl was significantly lower (by 45%). But, pharmacokinetic parameters of verapamil and norverapamil after oral administration of 50 mg/kg were no significant differences between UC and normal rats. The better absorption and poor excretion for low-dose verapamil may be attributed to down-regulation of P-gp expression in the intestine and kidney. No significant differences of pharmacokinetic parameters for high-dose verapamil may be explained as the saturation of an efflux mechanism. The findings of this study suggested that in UC patients, doses of verapamil should be decreased when low-dose verapamil was orally administrated.